Network push notification mobile apps for Johnson Controls / Siti Hajar Mohd Badri - Mohd Badri, Siti Hajar (2015)
In this paper, we present technology based push notification for android and integration with the cloud platforms. This notification system allows users to monitor the network at the company so that was always available for use with the downloaded application in Android smartphone users can receive notifications or alerts if there is any breakdown in their network. Thus, users can immediately attend the breakdown and solve issues that arise based on information send to the smartphone. The information contains detail devices such as IP address, device name, date and time occurs. The problem can be solved immediately and can reduce downtime.